2019
DOI: 10.3126/nmcj.v21i4.27630
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Medicine Utilization Pattern in Outpatient Departments of Tertiary Care Centre in Kathmandu

Abstract: The main objective of this study is to analyze the prescribing pattern of medicine in outpatient departments of tertiary care centre in Kathmandu using World Health Organization (WHO) drug use prescribing indicators. As per WHO consideration, 100 prescriptions were taken from each outpatient departments (OPD) of Nepal medical college including Orthopedics, Obstetrics and Gynecology, Surgery, Medicine, Ophthalmology, Otorhinolaryngology, Pediatrics, Dermatology and Psychiatry. Analysis of variance (ANOVA) was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 23 publications
(27 reference statements)
2
4
0
Order By: Relevance
“…In contrast of our study, Rimoy et al [18] reported that bendrofluazide was the most prescribed diuretics in the outpatient setting. Similar to our study, Furosemide was the most prescribed diuretics as reported by Thapa and Singh [19] and by Shalavadi et al [20].…”
Section: Discussionsupporting
confidence: 92%
“…In contrast of our study, Rimoy et al [18] reported that bendrofluazide was the most prescribed diuretics in the outpatient setting. Similar to our study, Furosemide was the most prescribed diuretics as reported by Thapa and Singh [19] and by Shalavadi et al [20].…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, higher results were recorded in studies from different parts of Ethiopia (ranging from 1.9 to 3), 22,[24][25][26][27][28][29][30][31] and other developing countries (ranging from 2.30 to 3.98). 32,34,35,37,40,43,44,46,48,49,54 On the contrary, the average number of medicines per prescription within the acceptable range was reported by other studies from Ethiopia (ranging from 1.65 to 1.8). 17,18,36 The prescription of many medicines for a patient may decrease adherence to treatment, increase the cost of medicine incurred by the patient, elevate the risk of drug interaction, and expose the patient to unnecessary potential side effects of the medication.…”
mentioning
confidence: 72%
“…14,65 Similarly, prescription of medicine by generic name is below the optimal value in most of the previous studies in different parts of Ethiopia (ranging from 79.2%to 99.25%), [22][23][24][25][26][27][28][29][30][31]36 and many other developing countries (ranging from 0% to 95.4%). 32,34,37,43,44,[46][47][48][49]52,53,55 However, results per the WHO/INRUD expectation were obtained in the study done at West Shewa Zone, Oromia, Ethiopia (100%) 17 and at 4 different emirates, UAE (100%). 50 In lowincome countries like Ethiopia where resources are often scarce, generic prescribing substantially reduces the cost of medicine paid by patients as well as the cost of medicine incurred by facilities because generics are relatively affordable, accessible, and recallable compared to brand counterparts.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…17,18 In this study, the number of prescriptions encountered with injection was low (1.8%). Recent studies conducted in hospital outpatients in Kathmandu, Nepal (1.5) 25 , central Nepal (0.7) 18 also reported lower values of injectable been prescribed. However, a survey performed in hospitals of south Ethiopia (38.1%) 26 and Iran (41%) 27 has shown higher rates of injectable encounters in prescriptions.…”
Section: Discussionmentioning
confidence: 91%